Web Based Archives at Pt Dupoin Palembang Branch As an Effort to Transform the Manual System To the Electronic System - Sultan Raka Adiatma; Dedi Haryanto; Apriansyah (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In Indonesia, digital transformation has become a national strategy encouraging both public and private institutions to adopt information technology to improve efficiency and accountability. One important form of this transformation is the implementation of a web-based digital archiving system that enables centralized document storage, management, and access. Web-based systems are preferred due to their flexibility, multi-device accessibility, and cost efficiency. In the context of document management, such systems provide fast document retrieval, systematic classification, and enhanced data security through user authorization. This research identifies problems at PT DUPOIN Palembang Branch, where document archiving is still handled manually using physical filing cabinets, leading to inefficiency, risk of data loss, and human error. The purpose of this study is to transform the conventional archiving process into a web-based digital archive system to improve work effectiveness and service quality. Data were collected through observation, interviews, and documentation. The results are expected to show that the implementation of a web-based archive system allows documents to be accessed online anytime and anywhere, supports remote work conditions, and improves document traceability through metadata management. This system is anticipated to strengthen document governance and enhance organizational competitiveness.